Immunomodulatory Effects of Lenvatinib Plus Anti–Programmed Cell Death Protein 1 in Mice and Rationale for Patient Enrichment in Hepatocellular Carcinoma. Issue 5 (27th September 2021) - Torrens, Laura; Montironi, Carla; Puigvehí, Marc; Mesropian, Agavni; Leslie, Jack; Haber, Philipp K.; Maeda, Miho; Balaseviciute, Ugne; Willoughby, Catherine E.; Abril‐Fornaguera, Jordi; Piqué‐Gili, Marta; Torres‐Martín, Miguel; et al.
Abstract : Background and Aims: Lenvatinib is an effective drug in advanced HCC. Its combination with the anti‐PD1 (programmed cell death protein 1) immune checkpoint inhibitor, pembrolizumab, has generated encouraging results in phase Ib and is currently being tested in phase III trials. Here, we aimed to explore the molecular and immunomodulatory effects of lenvatinib alone or in combination with anti‐PD1. Approach and Results: We generated three syngeneic models of HCC in C57BL/6J mice (subcutaneous and orthotopic) and randomized animals to receive placebo, lenvatinib, anti‐PD1, or combination treatment. Flow cytometry, transcriptomic, and immunohistochemistry analyses were performed in tumor and blood samples. A gene signature, capturing molecular features associated with the combination therapy, was used to identify a subset of candidates in a cohort of 228 HCC patients who might respond beyond what is expected for monotherapies. In mice, the combination treatment resulted in tumor regression and shorter time to response compared to monotherapies ( P  < 0.001). Single‐agent anti‐PD1 induced dendritic and T‐cell infiltrates, and lenvatinib reduced the regulatory T cell (Treg) proportion. However, only the combination treatment significantly inhibited immune suppressive signaling, which was associated with the TGFß pathway and induced an immune‐active microenvironment ( P  < 0.05 vs. other therapies). Based on immune‐related genomic profiles in human HCC, 22% of patients were identified as potential responders beyond single‐agent therapies, with tumors characterized by Treg cell infiltrates, low inflammatory signaling, and VEGFR pathway activation. Conclusions: Lenvatinib plus anti‐PD1 exerted unique immunomodulatory effects through activation of immune pathways, reduction of Treg cell infiltrate, and inhibition of TGFß signaling. A gene signature enabled the identification of ~20% of human HCCs that, although nonresponding to single agents, could benefit from the proposed combination.